2010
DOI: 10.1002/app.31949
|View full text |Cite
|
Sign up to set email alerts
|

Flame‐retardant properties of soybean fabric modified with N‐methylol diakyl phosphonopropionamide

Abstract: Soybean is a competitive production material for fibers as it is abundant and cost effective. However, an inherent deficiency of soybean fiber is its poor flame-retardant performance. In this study, the effect of N-methylol diakyl phosphonopropionamide (Pyrovatex CP) on the flame retardancy of soybean was investigated by the Limiting Oxygen Index (L.O.I.) and the vertical flammability test. Little benefit with regard to flame retardancy was found when soybean was treated with Pyrovatex CP in the absence of add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Kapura (1994) found using NMR and HPLC analysis that Pyrovatex CP does not consist of an individual compound but of several species based on dimethoxyphosphorylpropionamide. The effect of Pyrovatex CP on the flame retardancy of soybean has been recently studied (Vynias, 2010). The results indicated, Table 5, a slight increase in the L.O.I.…”
Section: Pyrovatex Cp As Flame Retardant Reagent For Soybean Fabricsmentioning
confidence: 97%
See 1 more Smart Citation
“…Kapura (1994) found using NMR and HPLC analysis that Pyrovatex CP does not consist of an individual compound but of several species based on dimethoxyphosphorylpropionamide. The effect of Pyrovatex CP on the flame retardancy of soybean has been recently studied (Vynias, 2010). The results indicated, Table 5, a slight increase in the L.O.I.…”
Section: Pyrovatex Cp As Flame Retardant Reagent For Soybean Fabricsmentioning
confidence: 97%
“…Tesoro et al (1969) have demonstrated the synergistic effect of nitrogen on phosphorus compounds, resulting in enhanced flame retardancy, with the application of a melamine formaldehyde compound in a phosphonate flame-retardant finishing. Therefore, an etherified methylolated melamine reagent (Lyofix MLF), was incorporated into the pad formulation with the expectation to enhance flame retardancy (Vynias, 2010 The inclusion of Lyofix MLF at 3% w/v application level enhanced flame retardancy compared to the Pyrovatex CP treatment alone, Table 5. This finding is not unexpected as melamine resins have been reported to be the most effective reagents for P-N synergism for cotton (Wu et al, 2003/Wu et al, 2006.…”
Section: Pyrovatex Cp As Flame Retardant Reagent For Soybean Fabricsmentioning
confidence: 99%
“…Nonetheless, as aforementioned, at the end of the twentieth century, there was a growing attention on eco-friendly natural-based sustainable biodegradable fibers due to ecological concerns, which leads to the awakening of promising soybean protein fiber. Key technological developments also provide opportunity for soybean protein fiber production with an ecologically friendly route leading to renewed interest [10][11][12][13]. Soybean cultivation has recently become much more cost-effective and soybean is one of the most abundant agricultural crops [14].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, soybean is cheap and abundant [6]. Furthermore, recent technical performance enhancement of soybean protein fiber via geneticengineering techniques extends the commercial scope of this fiber [10,11]. Therefore, in the 2000s, new soybean protein fiber, made from soybean protein and polyvinyl alcohol, was developed and a new soybean fibers' production process commercially promoted, standardized and launched to the textile markets [1].…”
Section: Introductionmentioning
confidence: 99%